Multi-resistant Pseudomonas aeruginosa ST235 in cystic fibrosis. (June 2018) - Lee, Annabelle C.; Jones, Andrew L.
Abstract: Chronic Pseudomonas aeruginosa infection is associated with a decline in lung function and overall poorer prognosis in the cystic fibrosis population. Molecular typing of P. aeruginosa has identified multiple clonal strains with increased virulence and transmissibility. P. aeruginosa ST235 is an emerging clonal strain with multi-drug resistance and is associated with more virulent infections. Novel cephalosporins, which have recently been introduced to clinical practice, may have higher efficacy against multi-drug resistant bacteria.